Seminal characteristics of ovine under environmental conditions of Colombian Caribbean - Carrascal-Triana, Erly Luisana (2022)
The aim of this study was to evaluate the seminal characteristics and the physical and functional conditions of native and introduced sheep breeds under the environmental conditions of the Colombian Caribbean. In total, 117 Santa Inés, Dorper, Katahdin and Ovinos de Pelo Colombiano (OPC) rams older than 11 months were evaluated for 14 months. The animals were from 18 farms of the departments of Córdoba, Sucre, Bolívar, Cesar and La Guajira. The physical-functional examinations of the males were carried out, as well as the macroscopic and microscopic characteristics of the semen. There were no differences (p>0.05) between breeds, departments and collection methods for the variables testicular volume, testicular length and width, scrotal circumference and testicular tone. In the humid Caribbean, mass motility was 76.36 ± 6.13% and the sperm concentration was 2707 ± 573x106 sperm/ml as compared to those found in the dry Caribbean (64.41 ± 5.45% and 962 ± 509.72 x106 sperm/ml, respectively). Semen collection method had a significant influence (p<0.05) on ejaculate volume, viability, vigour and sperm concentration. Seminal parameters were higher in the second and third trimester of the year and the relative humidity of the Caribbean had a significant effect on testicular volume (r=-0.23) and sperm abnormalities (r=0.29). It is concluded that the Santa Inés, Dorper, Katahdin and OPC sheep have satisfactory and viable characteristics for their reproduction in the Colombian Caribbean.